Agglomeration, Differentiation and Creative Milieux: A Socioeconomic Analysis of Location Behaviour of Creative Enterprises in Shanghai. Issue 1 (2nd January 2018) - He, Jinliao; Huang, Xianjin
Abstract: This paper presents an empirical study on the location choice of creative enterprises in Shanghai. It is suggested that categorical differences between different subsectors of creative industries are significant, especially with regard to a division between technology-intensive sectors and culture-related agencies. Creative enterprises from technology-intensive sectors such as architecture design and IT enterprises appear to differ greatly from cultural and fashion related agencies in location choice due to the disaggregated knowledge inputs involved in the production processes, as well as the divergences in market operation. Meanwhile, this study suggests that some location variables for creative industries (e.g. human capital and face-to-face contact) highlighted by West-based studies on the "creative class" are relevant in the case of Shanghai while other factors like sexual tolerance bear minor importance.